油用萝卜的研究现状及展望Research status and prospect of oilseed radish - 张小康1，张雪清1，熊秋芳2 ZHANG Xiaokang1, ZHANG Xueqing1, XIONG Qiufang2 (Zhongguo youzhi, 2023)
为带动我国油用萝卜产业的快速发展，促进以食用油为主，多产业（中药、芽苗、绿肥）协同发展局面的形成，系统概述了有关油用萝卜育种、栽培及管理，萝卜籽组成成分及功能，萝卜籽油加工技术方面的研究进展，论述了我国油用萝卜发展面临的问题，提出了相关建议，并展望未来油用萝卜产业的发展趋势及方向。油用萝卜品种类型丰富，适应性广，是一种具有推广应用潜力的新型油料作物品种。In order to promote the development of oilseed radish industry in China, and the formation of edible oil as the main, multi-industry (traditional Chinese medicine, sprouts, green fertilizer) coordinated development situation, the research progress in breeding, cultivation and management of oilseed radish, composition and function of radish seed, and processing technology of radish seed oil were systematically summarized. The problems faced by the development of oilseed radish in China were discussed, relevant suggestions were proposed, and the development trend and direction of oilseed radish industry were looked forward. Oilseed radish has a wide variety of varieties and adaptability, making it a new type of oilseed crop with great potential for promotion and application.